Multi - Industry Directorship dan Firm Value Pada Perusahaan Dalam Indeks Sri Kehati - Salis Musta Ani; Tri Astuti (Jurnal Akuntansi, 2023)
The purpose of this study is to examine the existence of the SRI Kehati index in Indonesia Stock Exchange through testing governance variables (multi-industry commissioners and directorships, independence of commissioners) in companies of the SRI Kehati index as a driver of firm value. The reseach is a quantitative research by pannel data with random effect models. The results showed that the presence of directors handle multiple industries was able to encourage an increase in form value. Likewise, independent commisioners are able to increase firm value. The results of this study contribute to an overview of the level of readliness of companies in implementing the Sustainability Disclosure Standardand and indicate factors that can encourage an increase in firm value by paying more attention to social and environmental issues so that it can benefit public companies in general in the context of developing sustainability in Indonesia. Keywords: Busy Director, Multy-Industry Directorship, Rating SRI Kehati, Sustainability